PERAN KEPALA DESA DALAM MENINGKATKAN PEMBANGUNAN DI DESA BOTUGOLU KECAMATAN BUNOBOGU KABUPATEN BUOL - Baharuddin, Alhamid; Nurbaya; Kartika, Ayu (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2025)
This research employed a descriptive qualitative method with observation, interviews, and documentation techniques. Data analysis was based on the Miles and Huberman model, encompassing data collection, presentation, and verification. The results indicate that the village head plays a crucial role in the development of Botugolu Village through participatory, communicative, and transparent leadership. Support comes from collaboration with village officials, the Village Consultative Body (BPD), and the community, fostering a sense of ownership and mutual cooperation. However, challenges such as lack of equitable participation, limited budget and infrastructure, and limited technological literacy need to be addressed to ensure more inclusive and sustainable development.